Optimization of Taxes and Tax System of Uzbekistan (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article deals with the topical issues of tax optimization in Uzbekistan, which have become especially important in the context of global economic changes. The article discusses the tax reforms, their impact on the economic environment and fiscal stability of the country. The main attention is paid to reducing the tax burden on business, combating the shadow economy and introducing digital technologies in tax administration. prospects for further development of the tax system, including the need to simplify procedures and expand digital platforms. The results of the study confirm that a comprehensive approach to reforming and digitalizing the tax system can create a more efficient and transparent tax administration in Uzbekistan.